Bone health and glucocorticoid‐containing lymphoma therapy — a review of risk factors and preventative measures. (2nd March 2022) - Eyre, Toby A.; Jensen, Paw; Booth, Stephen; El‐Galaly, Tarec Christoffer
Abstract: With survival outcomes ever improving for patients with a wide range of lymphoma histologies, the focus on reducing long‐term complications of therapy has increased. Recently published, complimentary population and retrospective series have highlighted the importance of considering bone health in patients treated for lymphoma. Fracture‐related events or the requirement for secondary bone prophylaxis, likely linked to glucocorticoid‐induced osteoporosis (GIO) are substantial and clinically meaningful in a significant minority of patients following routinely employed steroid‐containing immunochemotherapy. In this review, we describe the pathophysiology of GIO, the risk of GIO in observational front‐line lymphoma studies and efficacy of prophylactic measures from several prospective clinical trials are summarized. Finally, areas of importance for future research are discussed and recommendations for GIO risk assessment and management in lymphoma are provided based on the current available literature.